The implementation of MSMEs Protection Policies during the Covid-19 Pandemic - Sri Haryaningsih; Yulius Yohanes; Nahot Tua Parlindungan Sihaloho; Farah Devi Andriani (Khazanah Sosial, 2022)
During the crisis in the last two years, the government implemented five policy schemes to protect Micro, Small, and Medium Enterprises (MSMEs). This research aims to seek how the policies scheme recovers MSME activities and provides recommendations to distribute the policies benefits evenly. This qualitative research was conducted through a literature review design. Data were collected from laws and regulations, empirical research results, and credible newspapers. Data were analyzed using the theory of Mazmanian & Sabatier (1983). This research finds that not all MSMEs can recover sales, funding, supply, operations, and diversification. Problem characteristics and policy characteristics have been mapped according to the policy scheme. However, the goals achieved are more influenced by variables outside the law. Not all MSMEs meet bankable criteria and integrate with the digital ecosystem. As a structural problem, these situations can be overcome through a derivative policy with a top-down pattern. As a cultural problem, these situations require an MSMEs mindset change. Therefore, this research recommends MSMEs' digitalization through expanding fund access and protection (insurance). This research concludes that the protection of MSMEs is only effective for the integrated digital ecosystem. Thus, a derivative policy is needed to "force" MSMEs' digitalization ecosystem.